2016
DOI: 10.5455/medarh.2016.70.256-260
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Neutrophils/Lymphocyte Ratio in Rectal Cancer Patients with Preoperative Chemoradiotherapy

Abstract: Background:Several studies have reported that an elevation in neutrophils/lymphocyte ratio (NLR) is correlated with poor survival in patients with colorectal cancer, but in rectal cancer (RC), it has been reported only in a few studies. It is necessary to separate colon cancer and rectal cancer to clarify the prognostic significance of NLR, especially in patients who received chemoradiotherapy.Methods:It is a comparative, observational retrospective study of a cohort of 175 patients. We grouped the patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…In the ROC analysis, we failed to identify an appropriate cut-off value because the area under the curve for NLR was 0.555 [95% confidence interval (CI), 0.467–0.642; P=0.223] for the 3-year OS and 0.558 (95% CI, 0.477–0.638; P=0.159) for the 3-year DFS. Finally, an NLR ≥3.0 was considered as elevated NLR on the basis of previous studies [ 20 , 21 ]. There were 63 (31.2%) patients with NLR ≥3.0 and 139 (68.8%) patients with NLR <3.0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ROC analysis, we failed to identify an appropriate cut-off value because the area under the curve for NLR was 0.555 [95% confidence interval (CI), 0.467–0.642; P=0.223] for the 3-year OS and 0.558 (95% CI, 0.477–0.638; P=0.159) for the 3-year DFS. Finally, an NLR ≥3.0 was considered as elevated NLR on the basis of previous studies [ 20 , 21 ]. There were 63 (31.2%) patients with NLR ≥3.0 and 139 (68.8%) patients with NLR <3.0.…”
Section: Resultsmentioning
confidence: 99%
“…We did not find an association of NLR with OS (HR, 1.066; 95% CI, 0.681–1.668; P=0.779) or DFS (HR, 0.863; 95% CI, 0.536–1.390; P=0.542) using 3.0 as a cut-off value ( Figures 1 , 2 ). Furthermore, we repeated survival analyses using different cut-off values (2.0 [ 21 ] and 4.0 [ 22 ]) and again did not find an association between NLR and survival outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies [ 49 51 ] have shown correlation between the SIR and clinical outcomes in various cancers; However, conflicting evidence exists regarding the effects of PLR and LMR on the prognosis of CRC patients. In this meta-analysis of 33 studies which includes 15,404 cases, we reevaluated the prognostic roles of the PLR and LMR in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Lino-Silva and colleagues reported that there were no differences in survival outcomes or pCR rate according to NLR cut-off point (2.0, 2.5, 4, and 5) in 175 patients who underwent preop-CRT. [ 26 ] Shen and colleagues also reported that NLR measured in pre-CRT did not predict OS or disease-free survival (DFS) in patients with locally advanced rectal cancer who underwent preop-CRT. [ 27 ] Jung et al reported that NLR measured before commencement of preop-CRT could not discriminate recurrence-free survival (p = 0.07) among 984 patients who underwent preop-CRT.…”
Section: Introductionmentioning
confidence: 99%